Pattern of interaction and relationships between family members - Alazzam, Manar; Albashtawy, Mohammed; Aljezawi, Maen; Batiha, Abdul-Monim; Freij, Mazen; Khasawneh, Barakat; Alhalaiqa, Fadwa (International Journal of Health, 2017)
Studying a family as a unit to describe the relationships in will allow the researcher to investigate the family as the primary unit and as a whole, which means that the family, the individuals as family members and their relationship is in the foreground. The data derived using this approach comes from the family unit functioning as a whole and does not reflect the individual membersâ€™ contributions â€œsolelyâ€ or in a combined way. Such an approach allows for more global understanding of the issues surrounding family relationships as health and social data can be collected from different aspects and dimensions within the family as a unit and it will add more significant data. Even though studying a family as a unit eliminates the non-independence issue it does raise concerns about ignoring many potentially important details of intra-family relationships. In conclusion, the premise of studying the family as a unit (family as the unit of analysis) is that the researcher can gain greater insight into families in general and a familyâ€™s relationships in particular.